2012
DOI: 10.1111/j.1538-7836.2012.04824.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased anticoagulant response to low‐molecular‐weight heparin in plasma from patients with advanced cirrhosis

Abstract: Summary.  Introduction:  Cirrhotic patients may present thrombotic complications that warrant anticoagulant therapy. However, the efficacy of low-molecular-weight heparin (LMWH) in this clinical setting is still unclear. Aims/methods:  To evaluate the in vitro effect of LMWH on thrombin generation (TG) in cirrhotic patients at different stages of liver disease. Thirty cirrhotics (10 Child Pugh A, 10 Child Pugh B and 10 Child Pugh C), 10 subjects with inherited type 1 antithrombin (AT) defect and 10 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 13 publications
8
82
2
Order By: Relevance
“…Indeed, by using TGT, we recently demonstrated that the capacity of LMWH to inhibit thrombin formation in plasma of patients with chronic liver disease in vitro was consistent among samples of patients and controls, with the exception of patients with severe cirrhosis who showed a decreased response to the anticoagulant action of the drugs [123]. Interestingly, when using the same test, another group had found a more profound and disease stage-dependent anticoagulant effect of the drugs in cirrhotic plasma compared to normal plasma [124]. This difference in results may be attributed to different pre-analytical conditions highlighting, as with all assays, the necessity for methodological standardization in order to compare or interpret future in vivo dose-response studies of antithrombotic agents in cirrhosis.…”
Section: Monitoring Of Antithrombotic Therapymentioning
confidence: 88%
“…Indeed, by using TGT, we recently demonstrated that the capacity of LMWH to inhibit thrombin formation in plasma of patients with chronic liver disease in vitro was consistent among samples of patients and controls, with the exception of patients with severe cirrhosis who showed a decreased response to the anticoagulant action of the drugs [123]. Interestingly, when using the same test, another group had found a more profound and disease stage-dependent anticoagulant effect of the drugs in cirrhotic plasma compared to normal plasma [124]. This difference in results may be attributed to different pre-analytical conditions highlighting, as with all assays, the necessity for methodological standardization in order to compare or interpret future in vivo dose-response studies of antithrombotic agents in cirrhosis.…”
Section: Monitoring Of Antithrombotic Therapymentioning
confidence: 88%
“…In nonrandomized studies [44,45], LMWH administration at a fixed dose was effective and safe in patients with established PVT. In vitro the anti-Xa assay proved suboptimal for monitoring LMWH use [46,47], while TGA was more appropriate [47]. An in vitro study also suggested that, despite of a lower anti-thrombin level, plasma from patients with cirrhosis was more responsive to LMWH than that from healthy subjects [47].…”
Section: Low Molecular Weight Heparin (Lmwh)mentioning
confidence: 99%
“…In vitro the anti-Xa assay proved suboptimal for monitoring LMWH use [46,47], while TGA was more appropriate [47]. An in vitro study also suggested that, despite of a lower anti-thrombin level, plasma from patients with cirrhosis was more responsive to LMWH than that from healthy subjects [47]. The only available randomized trial showed that LMWH at a fixed dose and without laboratory monitoring was effective and safe in preventing PVT in patients with cirrhosis [48].…”
Section: Low Molecular Weight Heparin (Lmwh)mentioning
confidence: 99%
“…In absence of previous history and/or other risk factors for hemorrhagic complications [21,22], low-molecular-weight heparin likely represents the safest choice of systemic anticoagulation in cirrhotic patients with extensive portal vein (and/or mesenteric) thrombosis without increasing the risk for VB [23]. However, clinicians should always be aware of the fact that (despite decreased antithrombin III concentrations) its anticoagulation effect in vivo remains practically unaffected [24]. More aspects of 'hemostasis dysregulation' are shown by Drolz et al [25] in this focus issue of Visceral Medicine.…”
Section: Hemostasis Dysfunctionmentioning
confidence: 99%